Climate change and food security in EAC region: a panel data analysis - Walaa, Mahrous (Emerald, 2019)
Purpose This study aims to analyze the impact of global climate change on food security in the East African Community (EAC) region, using panel data analysis for five countries, over 2000-2014. Design/methodology/approach The determinants of food security are expressed as a function of rainfall, temperature, land area under cereal production, and population size. The paper used pooled fixed effects to estimate the relationship among these variables. Findings Findings show that food security in EAC is adversely affected by temperature. However, precipitation and increasing areas cultivated with cereal crops will be beneficial to ensure everyone's food security. Originality/value Actions for mitigating global warming are important for EAC to consolidate the region’s economic, political and social development/stability